2015
DOI: 10.1590/2317-1782/20152014117
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic reflex on newborns: the influence of the 226 and 1,000 Hz probes

Abstract: PURPOSE: To analyze the occurrence of acoustic reflex and its threshold on newborns using the 226 and 1,000 Hz probes. METHODS: Thirty-six newborns with "PASS" results in newborn hearing screening and tympanogram with one or two peaks for both probe tones were included. Group I comprised 20 full-term newborns without risk indicator for hearing loss, and Group II comprised 16 newborns with at least one risk indicator. The study about ipsilateral acoustic reflex thresholds was conducted in 500, 1,000, 2,000, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Traditionally, a 226 Hz probe tone has been used but researchers have found that using a highfrequency probe tone (>800 Hz) to be more effective in neonates because the ASR is present more often in normal ears at lower activation levels (De Lyra-Silva, Sanches, Neves-Lobo, Ibidi, & Carvallo, 2015;Jacob-Corteletti et al, 2015;Mazlan, Kei, & Hickson, 2009a;Weatherby & Bennett, 1980). An activating tone of 2000 Hz or BBN has been recommended for testing neonates (De Lyra-Silva et al,…”
Section: Acoustic Stapedial Reflexesmentioning
confidence: 99%
“…Traditionally, a 226 Hz probe tone has been used but researchers have found that using a highfrequency probe tone (>800 Hz) to be more effective in neonates because the ASR is present more often in normal ears at lower activation levels (De Lyra-Silva, Sanches, Neves-Lobo, Ibidi, & Carvallo, 2015;Jacob-Corteletti et al, 2015;Mazlan, Kei, & Hickson, 2009a;Weatherby & Bennett, 1980). An activating tone of 2000 Hz or BBN has been recommended for testing neonates (De Lyra-Silva et al,…”
Section: Acoustic Stapedial Reflexesmentioning
confidence: 99%